Biometric Systems and Technologies: Concepts, Types, Functions and Legal Fundamentals in EU Law - Hachkevych, Andrii (Problems of legality, 2026)
The issue raised is relevant, firstly, to the growing implementation of biometric systems and technologies across various fields due to the development of artificial intelligence, and secondly, to the corresponding increase in risks and threats associated with their use. The purpose of this article is to explore the theoretical and methodological approaches to studying the use of biometric systems and technologies. It will also address the legal foundations surrounding their regulation, taking into account the provisions of the EU legislation, as well as law enforcement practices. This includes examining decisions made by the European Court of Justice, as well as supervisory authorities of EU member states regarding personal data protection. In this research, the author employed several methods: classification, to explain the existing capabilities of biometrics; comparison, to differentiate between biometric identification (determining identity) and verification (checking identity) as the key functions of biometric systems and technologies; systematization, to compile a list of the most important acts of EU legislation on biometrics, which will serve as guidelines for Ukrainian legislators; and analysis, to examine law enforcement practice. The author describes biometric technologies as a type of technology that processes biometric data for personal identification. A biometric system is defined as an information system that, by converting a person's biological characteristics into a machine-readable format and analyzing them, establishes both a link between biometric data samples, thereby facilitating personal identification, or a belonging of a person to a particular group. In the article, biometric systems and technologies are classified based on the type and number of biological characteristics used, the need for physical contact, and their range of applications. The results of the study reveal contradictions arising from the adoption of biometrics, as confirmed by EU law applications, particularly regarding the justification for the collection, storage, and use of fingerprints and other biometric identifiers without an individual's explicit consent. This underscores the need to improve legal regulation. The article concludes that, alongside provisions on the protection of personal data, an important role in determining the use of biometric systems and technologies is played by both legislation regarding artificial intelligence and legal support for the sectoral implementation of biometric technologies.